Local government strategies for providing Adequate Housing Infrastructure, Facilities, and Public Utilities (PSU) in Lamandau Regency - Timbung, Mancini Pratama (Priviet Social Sciences Journal, 2026)
Housing development in Lamandau Regency has grown alongside rising demand, but the adequacy of housing Infrastructure, Facilities, and Public Utilities (PSU) remains uneven and often falls short of technical standards. This gap increases the risk of poor accessibility, inadequate basic services, and delayed PSU handovers from developers to the local government. This study examines local government strategies for ensuring adequate and sustainable PSU housing provision in Lamandau Regency. This study adopts a descriptive qualitative approach using triangulation through in-depth interviews with key stakeholders (local agencies, developers, and communities), field observations in housing areas, and a documentation review of relevant regulations and technical archives. pasted SWOT analysis was employed to identify the internal and external factors shaping PSU governance and to formulate actionable strategic directions. The findings indicate persistent implementation problems, including substandard road and drainage quality, incomplete PSU delivery against approved site plans, and reactive supervision that intensifies only near the handover requests. The study concludes that Lamandau needs a shift from reactive to proactive, integrated, and law-enforcement-based governance through four pillars: harmonized inter-agency SOPs and an integrated verification team, mandatory financial guarantees and consistent sanctions, GIS-based asset monitoring, and optimized financing by leveraging central government programs and bank guarantees to rectify problematic assets.